DAMPAK BANTUAN PAKET SEMBAKO DAN BANTUAN LANGSUNG TUNAI TERHADAP KELANGSUNGAN HIDUP MASYARAKAT PADALARANG PADA MASA PANDEMI COVID 19 - NUNIEK DEWI PRAMANIK (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The impact of basic food package assistance and direct assistance to the survival of Padalarang community at the time of Pandemic Garry 19. The purpose of this research is to know and analyze the help of basic food packages and direct cash assistance to give effect on the survival of the Padalarang community at the time of Pandemic Garry 19. The results of the study describing the help of basic food packages and direct assistance in cash, then it should be the city government of Padalarang in this case the local government of West Bandung district to improve the help of basic food packages and cash direct assistance, considering the survival of the residents of Pandemi Garry 19, the consequences of not earning money to finance their lives.